Synthesis of Acrylated Alkyd Resins from Castor Oil and Their Performance Evaluation in Environmental Implications for Coating Applications - Nadia Baqer Hussein; Doaa Jalil Al-Taie (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study presents the synthesis of acrylated alkyd resins derived from castor oil for environmentally-friendly coating applications. A novel approach to alkyd resin synthesis was developed and involved free-radical polymerization with acrylic monomers to enhance drying time, chemical resistance, and solubility. The method advantages controlled radical polymerization to optimize the acrylic-to-alkyd ratio and oil length, resulting in improved film properties, including higher crosslink density and faster drying rate compared to traditional methods. The study also focuses on challenges, such as the observed negative impact on certain film characteristics, which include reduced chemical resistance at high levels of acrylic modification. The limitations underscore the importance of balancing acrylic and alkyd phases to achieve optimal performance. Comprehensive physicochemical analyses, which include FTIR and 1HNMR, confirm the formation of the hybrid structure, while performance tests reveal significant advantages over conventional solvent-borne alkyds. This work establishes a foundation for advanced coating binders that combine sustainability with enhanced functionality while recognizing the need for further optimization to mitigate limitations at high modification levels.